Effect of zinc supplementation on morbidity due to acute diarrhoea in infants and children in Sanaa, Yemen: A randomized controlled double blind clinical trial - Elnemr, Muna A. M.; Abdullah, Ahmed K. (Sultan Qaboos University, 2007)
Objectives: To study the impact of zinc administration on the morbidity and mortality attributed to diarrhoea among children less than 5 years old. Methods: The study design was a randomized double blinded controlled clinical trial, held at Elsabeen Hospital for Maternity and Childhood, Sanaa, Yemen. The study was conducted during the period September 2005 to October 2006 on 180 children less than 5 years old with acute diarrhoeal episodes. They were randomly allocated to two groups; one of them received a placebo and the other received zinc acetate syrup for 14 days. Both groups were followed up for 2 months. Results: Zinc was able to decrease the mean number of diarrhoeal episodes: 1.39 in the intervention group versus 2.59 in the control group. It also reduced the mean frequency of stools per day in each attack (3.57 in the intervention group versus 5.47 in the control group) and the volume of stool in each attack during the follow-up period. Moreover, zinc was significantly more palatable. Conclusion: We can conclude from the study that administration of zinc for two weeks during acute diarrhoeal episodes could decrease the incidence of further diarrhoeal episodes as well as the severity of these episodes. The lower rates of child morbidity with zinc treatment represent substantial benefits from a simple and inexpensive intervention that can be incorporated in existing efforts to control diarrhoeal disease.